Prehospital continuous positive airway pressure (CPAP) for acute respiratory distress: a randomised controlled trial. Issue 1 (26th March 2021) - Finn, Judith C; Brink, Deon; Mckenzie, Nicole; Garcia, Antony; Tohira, Hideo; Perkins, Gavin D; Arendts, Glenn; Fatovich, Daniel M; Hendrie, Delia; McQuillan, Brendan; Summers, Quentin; Celenza, Antonio; et al.
Abstract : Objective: To compare the efficacy of continuous positive airway pressure (CPAP) versus usual care for prehospital patients with severe respiratory distress. Methods: We conducted a parallel group, individual patient, non-blinded randomised controlled trial in Western Australia between March 2016 and December 2018. Eligible patients were aged ≥40 years with acute severe respiratory distress of non-traumatic origin and unresponsive to initial treatments by emergency medical service (EMS) paramedics. Patients were randomised (1:1) to usual care or usual care plus CPAP. The primary outcomes were change in dyspnoea score and change in RR at ED arrival, and hospital length of stay. Results: 708 patients were randomly assigned (opaque sealed envelope) to usual care (n=346) or CPAP (n=362). Compared with usual care, patients randomised to CPAP had a greater reduction in dyspnoea scores (usual care −1.0, IQR −3.0 to 0.0 vs CPAP −3.5, IQR −5.2 to −2.0), median difference −2.0 (95% CI −2.5 to −1.6); and RR (usual care −4.0, IQR −9.0 to 0.0 min -1 vs CPAP −8.0, IQR −14.0 to −4.0 min -1 ), median difference −4.0 (95% CI −5.0 to −4.0) min -1 . There was no difference in hospital length of stay (usual care 4.2, IQR 2.1 to 7.8 days vs CPAP 4.8, IQR 2.5 to 7.9 days) for the n=624 cases admitted to hospital, median difference 0.36 (95% CI −0.17 to 0.90). Conclusions: The use of prehospital CPAP by EMS paramedics reduced dyspnoea and tachypnoea in patients with acute respiratory distress but did not impact hospital length of stay. Trial registration number: ACTRN12615001180505.